Emerging roles of non-coding RNA derived from extracellular vesicles in regulating PD-1/PD-L1 pathway: insights into cancer immunotherapy and clinical applications - Haixia Zhang; Lianfeng Gong; Li Yu; Chenge Xian; Zhaowu Ma; Xianwang Wang; Ruohan Xia (Cancer Cell International)
Abstract Numerous studies have demonstrated that extracellular vesicles (EVs) carry a variety of noncoding RNAs (ncRNAs), which can be taken up by neighboring cells or transported to distant sites via bodily fluids, thereby facilitating intercellular communication and regulating multiple cellular functions. Within the tumor microenvironment, EV-ncRNA, on the one hand, regulate the expression of PD-L1, thereby influencing tumor immune evasion, promoting tumor cell proliferation, and enhancing tumor growth, invasion, and metastasis in vivo. On the other hand, these specific EV-ncRNAs can also modulate the functions of immune cells (such as CD8 + T cells, macrophages, and NK cells) through various molecular mechanisms, inducing an immunosuppressive microenvironment and promoting resistance to anti-PD-1 therapy. Therefore, delving into the molecular mechanisms underlying EV-ncRNA regulation of immune checkpoints presents compelling therapeutic prospects for strategies that selectively target EV-ncRNAs. In this review, we elaborate on the cutting-edge research progress related to EV-ncRNAs in the context of cancer and dissect their pivotal roles in the PD-1/PD-L1 immune checkpoint pathway. We also highlight the promising clinical applications of EV-ncRNAs in anti-PD-1/PD-L1 immunotherapy, bridging basic research with practical clinical applications. Graphical Abstract